Characteristics and Outcomes of Blood Culture- Positive Versus Blood Culture- Negative Patients Admitted in Pediatric Intensive Care Unit in Chittagong Medical College Hospital (IAHS Medical Journal, 2022)
Background: Only a few studies investigated the association of a positive blood culture with mortality in the pediatric population, the predictive significance of a positive blood culture in children admitted to the Pediatric Intensive Care Unit (PICU) remains uncertain. This study aimed at evaluating the characteristics and outcomes of negative blood culture compared to those of positive blood culture in children admitted to the PICU of Chittagong Medical College Hospital (CMCH).Materials and methods: A retrospective cohort study was conducted at the PICU of CMCH. All pediatric patients, from 1 month to 12 years of age, admitted between October 2021 and March 2022were included in the study. All blood culture samples sent from patients hospitalized in the PICU of CMCH between October 2021 and March 2022, were evaluated retrospectively. Information collected includes the demographic data, Primary diagnosis, and outcome of the patients.Results: Of the 214 patients, 29 (13.6%) had a positive blood culture whereas 185 (86.4%) had a negative bacterial blood culture. Pneumonia was extremely common, present in 65.5% and 34% of the patients, respectively in culture positive and negative patients, and tended to result in a positive culture (p